Writing Competence and Lexical Diversity in EFL Context of Hungarian and Jordanian University Students - Naji, Ahmad; Rawshdeh, Ibrahim (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2024)
This study investigates the relationship between lexical diversity (LD) and writing competence in English as a Foreign Language (EFL) among 66 Hungarian and 64 Jordanian university students. After completing a bilingual language profile, participants wrote narratives following a silent film and were analyzed using Text Inspector. Results showed a significant positive correlation between writing competence scores and LD measures (VocD and MTLD) in both groups, with slightly higher scores for Hungarians. The Hungarian group had more participants at the C1 level, while Jordanians were predominant at B2. Gender differences in LD and writing competence were observed but not statistically significant. This research provides practical insights for educators, highlighting the correlation between writing competence and LD, and offering implications for effective language-learning strategies in the EFL context.